Identifying barriers and proposing a roadmap to develop industrial symbiosis projects - Abreu, Mônica Cavalcanti Sá de; Mota, Renata Castro; Paula, Eugênia Vale de (Revista de Administração da UFSM, 2020)
This article identifies barriers for the implementation of industrial symbiosis projects in companies located in the Industrial and Port Complex of Pecém (CIPP). The concept of industrial symbiosis (IS) has become a well-recognized approach for environmental improvements at the regional level. Many technical solutions for waste and by-product material, water, and energy reuse between neighboring industries (so-called synergies) have been discovered and applied in the IS examples from all over the world. However, the potential uptake of new synergies in the regions is often limited by a range of nontechnical barriers. This study adopted a qualitative approach and conducted semi-structured interviews with managers of companies in operation at CIPP. The results showed that low levels of trust, communication, and cooperation prevent companies from establishing waste exchange initiatives. The research also confirms the existence of social, technological, financial, regulatory, and institutional barriers for the implementation of industrial symbiosis projects. Companies in the CIPP are in the initial stage of maturity, which means they do not recognize possible benefits from industrial symbioses. The research proposes ways for greater engagement among companies, in the sense of guiding the development of industrial symbiosis projects. It is necessary to pay attention to the barriers identified in the CIPP, because they are not easily removed in the social and economic context of the vast majority of Brazilian industrial complexes.